Heterodox macroeconomics : models of demand, distribution and growth - Blecker, Robert A., 1956-; Setterfield, Mark, 1967- (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar Publishing, 2019)
The last few decades have witnessed an outpouring of literature on macroeconomic models in the broad 'heterodox' tradition of Marx, Keynes, Robinson, Kaldor and Kalecki. These models yield an alternative analytical framework in which the big questions of our day - such as how inequality is related to growth or stagnation, and whether long-run growth is stable or unstable - can be fruitfully addressed. Heterodox Macroeconomics provides an accessible, pedagogically oriented treatment of the leading models and approaches in heterodox macroeconomics with clear, step-by-step presentations of core m.
Core models of growth and distribution -- Extended models of distributional conflict and cyclical dynamics -- Kaldorian approaches : Export-led growth and the balance of payments constraint.
BIBINDX
Keywords: Macroeconomics -- Mathematical models